2015
DOI: 10.1111/azo.12134
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different diets on digestive enzyme activities, in vitro digestibility, and midgut gland structure in juvenile crayfish, Cherax quadricarinatus

Abstract: Sacrist an, H.J., Fern andez-Gimenez, A.V., Chaulet, A., Franco Tadic, L.M., Fenucci, J. and L opez Greco, L.S. 2015. Effect of different diets on digestive enzyme activities, in vitro digestibility, and midgut gland structure in juvenile crayfish, Cherax quadricarinatus. -Acta Zoologica (Stockholm) 00: 000-000.This study investigated the effects of food quality on digestive enzyme activities, in vitro protein digestibility and histological traits of the midgut gland in juvenile crayfish Cherax quadricarinatus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 77 publications
0
11
0
Order By: Relevance
“…However, a formulated feed for redclaw crayfish is not available in South America, so producers usually produce their own diet or use one that is formulated for trout (Fundus®). Sacristán et al () evaluated this diet and demonstrated that it is not suitable for C. quadricarinatus juveniles as they observed malnutrition signs in the midgut gland structure. In addition to this drawback, the cost of the commercial fish meal used as the main component of feed formulations is continuously increasing, while its market supply displays a considerable variation in quality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a formulated feed for redclaw crayfish is not available in South America, so producers usually produce their own diet or use one that is formulated for trout (Fundus®). Sacristán et al () evaluated this diet and demonstrated that it is not suitable for C. quadricarinatus juveniles as they observed malnutrition signs in the midgut gland structure. In addition to this drawback, the cost of the commercial fish meal used as the main component of feed formulations is continuously increasing, while its market supply displays a considerable variation in quality.…”
Section: Discussionmentioning
confidence: 99%
“…So far, a 100% efficient protein digestion has never been described, and such digestion effectiveness varies according to the protein source supplied (Sacristán et al, ; Smith, Lee, Lawrence, & Strawn, ). Thus, the expected future growth of the aquaculture sector increases the pressure to maximize feed utilization.…”
Section: Introductionmentioning
confidence: 99%
“…2016). Despite the delay in mortality (as shown, e.g., for yabby; Unestam, 1975), redclaw appears to be susceptible (Unestam 1975b; Roy 1993; Stephens et al . 2005) and can exhibit high mortality rates in aquaculture (Marino et al .…”
Section: Potential and Observed Biological Impactsmentioning
confidence: 96%
“…Diets currently used for red claw crayfish rely mostly on diets from shrimps, primarily Litopenaeus vannamei , Penaeus monodon and Macrobrachium rosenbergii , and even on fish diets (Saoud et al, 2013). Progress in the development of commercial feed for red claw crayfish has been made over the past decade, but many knowledge gaps still exist in nutrient requirements, which need to be researched extensively and deeply (Cortés‐Jacinto et al, 2003; Sacristán et al, 2016; Thompson et al, 2005).…”
Section: Introductionmentioning
confidence: 99%